Evitalizing social work practice : the community development conundrum - Sithole, Sello (Social Work / Maatskaplike Werk, 2017)
This paper is an amended version of the presentation made at the Social Work Indaba held 24-26 March 2015 in Durban. The problem that was investigated is whether it is desirable to teach community development in the undergraduate social work programme. A sample of academics in the Department of Social Work at the University of Limpopo was asked to express their views on this. Another available sample of social work practitioners was asked the same question. The findings from the two samples are divergent in that the academics insisted that community development should remain part of the university social work programme, whereas young practising social workers felt that it should be discontinued.
Journal article published in the journal of Social Work / Maatskaplike Werk Vol 53 No 3; Issue 1 doi:http://dx.doi.org/10.15270/53-3-571
Keywords: Social work practice; Community development; Undergraduate social work programme; Social work education -- South Africa; Social service; Community development -- South Africa